Trying out new cafes in town: Assessing the impact of café’s physical environment on visit intention - Chong, Daniel Ka Leong * (Universiti Teknologi MARA, 2018)
In the face of substantial investments in café physical environment set-up, café’s owners and managers are given little indication concerning their expensive set-up of a café’s overall effectiveness in driving consumer visit intention. This study of a café’s physical environment validates the importance of physical environment and its impact on the new consumers’ visit intention. This study hypothesized the new customers’ visit intention to a newly set-up café can be predicted by four physical environment factors: facility aesthetics, ambience, lighting and spatial arrangement. Online survey questionnaires were distributed to 200 respondents using convenience purposive sampling approach and Structural Equation Modelling was implemented to examine the hypothesized relationships. While facility aesthetics and lighting in their current form do offer some “pull-factor” building benefits, their effect on visit intention is significantly stronger than ambience and spatial arrangement within a café. Thus, the investment of café physical environment does deliver some advantage, but conceivably not in the way the owners and managers desires. The café owners and managers should consider the importance of facility aesthetics and lighting in café layout and engineering design rather than overly focus on ambience creation and space arrangement pertaining to tables and chairs layout and positioning.